EFEKTIVITAS PENGAWASAN SURAT PERSETUJUAN BERLAYAR DALAM MEWUJUDKAN KESELAMATAN DAN KEAMANAN BERLAYAR DI KANTOR UNIT PENYELENGGARA PELABUHAN KELAS I MOLAWE - Usman, Usman; Abbas, Bakhtiar; Supriadin, Nofal (JIM : Journal Of International Management, 2024)
This study aims to determine the Effectiveness of Supervision of Sailing Approval Letters in Ensuring Safety and Security of Sailing at the Office of Class I Port Operator Unit in Molawe. The research method used in this study is descriptive research with a qualitative approach. Data collection was conducted using observation, interviews, and documentation techniques. The researcher used source triangulation to check the validity of the research data. Data analysis in this study used three components consisting of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the effectiveness of supervision of sailing approval letters in ensuring safety and security of sailing at the Office of Class I Port Operator Unit in Molawe is already good. This can be seen from the requests from owners, agents, or ship captains, mutual declaration (statements of the ship captain), crew lists, cargo manifests, valid ship documents, payment of non-tax state revenue (PNBP), and issuance of sailing approval letters have been effective.